Motivational Design for Learning and Performance The ARCS Model Approach - Keller, John M.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
It is impossible to control another person$1 (Bs motivation. But much of the instructor$1 (Bs job involves stimulating learner motivation, and learning environments should ideally be designed toward this goal. Motivational Design for Learning and Performance introduces readers to the core concepts of motivation and motivational design and applies this knowledge to the design process in a systematic step-by-step format. The ARCS model$1 (Btheoretically robust, rooted in best practices, and adaptable to a variety of practical uses$1 (Bforms the basis of this problem-solving approach. Separate chapters cover each component of the model$1 (Battention, relevance, confidence, and satisfaction$1 (Band offer strategies for promoting each one in learners. From there, the motivational design process is explained in detail, supplemented by real-world examples and ready-to-use worksheets. The methods are applied to traditional and alternative settings, including gifted classes, elementary grades, self-directed learning, and corporate training. And the book is geared toward the non-specialist reader, making it accessible to those without a psychology or teaching background. With this guide, the reader learns how to: Identify motivation problems and goals Decide whether the environment or the learners need changing Generate attention, relevance, confidence, and satisfaction in learners Integrate motivational design and instructional design Select, develop, and evaluate motivational materials Plus a wealth of tables, worksheets, measures, and other valuable tools aid in the design process Comprehensive and enlightening, Motivational Design for Learning and Performance furnishes an eminently practical body of knowledge to researchers and professionals in performance technology and instructional design as well as educational psychologists, teachers and trainers.s
The Study of Motivation -- What is Motivational Design? -- The Arcs Model of Motivational Design -- Generating and Sustaining Attention -- Establishing and Supporting Relevance -- Building Confidence -- Managing Outcomes for Satisfaction -- Identifying Motivational Problems -- Identifying Motivational Goals and Tactics -- Integrating Motivational and Instructional Strategies -- Tools to Support Motivational Design -- Motivational Design Research and Development.
Keywords: Education; Educational psychology; Education; Educational Psychology; Learning & Instruction